THE EFFECT OF EDUCATION INDEX, HEALTH INDEX, EXPENDITURE INDEX ON POVERTY LEVELS: STUDY IN EAST JAVA PROVINCE - Mustofa, Moch. Zainal; Said, Abdullah; Amin, Fadillah (Erudio Journal of Educational Innovation, 2025)
This study employs a quantitative approach with multiple linear regression methods to examine the influence of the Education Index, Health Index, and Expenditure Index on poverty levels. The data analyzed show significant increases in the Education and Health Indexes during the period from 2012 to 2023. The Education Index rose from a minimum value of 38.29 to 51.73 and a maximum from 71.15 to 80.27. Meanwhile, the Health Index increased from a minimum value of 69.57 to 73.23 and a maximum from 82.77 to 84.48. Both indices exhibit a significant negative relationship with poverty levels, indicating that improvements in education and health contribute to the reduction of poverty.However, the Expenditure Index does not show a significant influence on poverty. This indicates that expenditure does not directly affect poverty in the region. Regression analysis results reveal that the tested model can explain approximately 66.9% of the variation in poverty levels using these three variables. Overall, this research reinforces the hypothesis that enhancements in the quality of education and health are crucial factors in poverty reduction strategies, while the influence of expenditure still requires further investigation.